Effects of the Prone Position on Regional Neutrophilic Lung Inflammation According to 18F-FDG Pet in an Experimental Ventilator-Induced Lung Injury Model. Issue 2 (February 2022) - Nakahashi, Susumu; Imai, Hiroshi; Shimojo, Nobutake; Magata, Yasuhiro; Einama, Takahiro; Hayakawa, Mineji; Wada, Takeshi; Morimoto, Yuji; Gando, Satoshi
Abstract : ABSTRACT: Ventilator-induced lung injury (VILI) can be life-threatening and it is important to prevent the development of VILI. It remains unclear whether the prone position affects neutrophilic inflammation in the lung regions in vivo, which plays a crucial role in the pathogenesis of VILI. This study aimed to assess the relationship between the use of the prone position and the development of VILI-associated regional neutrophilic lung inflammation. Regional neutrophilic lung inflammation and lung aeration during low tidal volume mechanical ventilation were assessed using in vivo 2-deoxy-2-[(18)F] fluoro-D-glucose ( 18 F-FDG) positron emission tomography and computed tomography in acutely experimentally injured rabbit lungs (lung injury induced by lung lavage and excessive ventilation). Direct comparisons were made among three groups: control, supine, and prone positions. After approximately 7 h, tissue-normalized 18 F-FDG uptake differed significantly between the supine and prone positions (SUP: 0.038 ± 0.014 vs. PP: 0.029 ± 0.008, P = 0.038), especially in the ventral region (SUP: 0.052 ± 0.013 vs. PP: 0.026 ± 0.007, P = 0.003). The use of the prone position reduced lung inhomogeneities, which was demonstrated by the correction of the disproportionate rate of voxel gas over the given lung region. The progression of neutrophilic inflammation was affected by the interaction between the total strain (for aeration) and the inhomogeneity. The prone position is effective in slowing down the progression of VILI-associated neutrophilic inflammation. Under low-tidal-volume ventilation, the main drivers of its effect may be homogenization of lung tissue and that of mechanical forces. Abstract : Supplemental Digital Content is available in the text